Differential mode of action of tricyclazole in vitro and in planta on Bipolaris sorokiniana causing spot blotch in barley - R. CHAND*; J.S. SRIVASTAVA, ANIRUDHA CHATTOPADHYAY, CHANDA KUSHWAHA, (Indian Phytopathology, 2013)
Tricyclazole, a melanin biosynthesis inhibitor is inhibiting the melanin related phenomenon like sporulation of Bipolaris sorokiniana causing spot blotch of barley. It reduces the spore size, average number of septation and extent of sporulation in fungi in vitro condition. But it have little role in spore germination of B. sorokiniana, while it reduces the disease development caused by Bipolaris in barley.